BUILDING A YEAR CYCLE OF TRAINING ATHLETES RADIO DIRECTION FINDERS AT THE STAGE OF IMPROVING SPORTS SKILLS - Zelensky, K.G.; Ponomarev, G.N.; Kostyuchenko, V.F.; Shubin, E.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to optimize the structure of the annual training cycle for qualified athletes aged 16-17 in sports direction finding. Methods and structure of the study. As a result of a longitudinal study (in the period from 2001 to 2021 with the participation of 39 athletes at the stage of improving sportsmanship), it was found that in sports radio direction finding, the single-cycle option for building a one-year training is optimal, when the preparatory period lasts from September to March, the competitive period from April to July, transitional - in August. Results and conclusions. It was revealed that with such periodization due to the purposeful use of various training tools and exercises that contribute to the improvement of the technique and tactics of operational radio direction finding, near radio search and orientation on the ground, the competitive period can be multi-peak, that is, athletes are able to repeatedly reach the peak of their sports form to the responsible and main (culminating) competitions.